Design and psychometric properties of a questionnaire to assess gender sensitivity of perinatal care services: a sequential exploratory study - Masoumeh Simbar; Fatemeh Rahmanian; Soheila Nazarpour; Ali Ramezankhani; Narges Eskandari; Farid Zayeri (BMC, 2020)
Abstract Background Providing gender sensitive reproductive health service is recently emphasized by health organizations. This study aims to develop and assess psychometric properties of a questionnaire to assess gender sensitivity of perinatal care services (GS-PNCS) to be used by managers of perinatal services. Methods This study is a mixed sequential (Qualitative-Quantitative) exploratory study. In the qualitative phase, 34 participants were interviewed and the items were generated. To evaluate the validity; face, content and construct validity were assessed. The reliability was assessed by internal consistency and stability calculation. Results The content validity and reliability were demonstrated by S-CVR = 0.92 and S-CVI = 0.98, Cronbach's α = 0.880 and the ICC = 0.980 to 0.947. Exploratory factor analysis showed 8 factors which explained more than 52.53% of the variance. Conclusion GS-PNCS is a valid and reliable questionnaire, with 49 items to assess gender sensitivity of perinatal care services and helps health care managers and planners to improve the quality of the services.